Beginning InfoPath 2003 - Barker, F. Scott (Wrox beginning guides., 2005)
* InfoPath creates forms for data gathering, analysis, and reporting * InfoPath has been adopted by many companies, ranging from Toyota and Hewlett-Packard to M/I Homes and New York Presbyterian Hospital, and recent laws that regulate data collection, such as Sarbanes-Oxley and HIPPA, have increased demand * Explains how to use InfoPath in a single user mode and how to use it with other databases, such as Access and SQL Server, or in conjunction with XML Web services * Shows how to deploy multi-user forms that use InfoPath with collaborative products such as Windows SharePoint Services and Biz.